Effects of home disease management strategies based on the dyadic illness management theory on elderly patients with chronic heart failure and informal caregivers’ physical and psychological outcomes: protocol of a randomized controlled trial - Hu, Yaoyao; Yu, Lu; Zhu, Lingyun; Li, Li; Li, Xiaojing; Wang, Xiaoyan; Zhou, Taihua; GU, Danfeng (Current controlled trials in cardiovascular medicine, 2024)
Currently, most elderly chronic heart failure (CHF) patients go home for rehabilitation after certain treatment in hospitals. However, the results of their rehabilitation at home are not satisfactory. According to studies, dyadic treatments can increase the efficiency of home rehabilitation, enhance both partners' quality of life, lessen the caregiver's load of care, and alleviate the strain of medical resources. Thus, the aim of our research is to design a study protocol that included elderly CHF patients and their informal caregivers as an intervention unit and to explore the impact of the protocol on their health and physical outcomes. This is a prospective randomized controlled trial conducted in a triple-A hospital. In total, 80 elderly CHF patients and informal caregivers (80 dyads) will be recruited with informed consent. Based on the randomized numbers, they are divided into a control group (40 dyads) and an intervention group (40 dyads), subjects in the control group will receive usual care, and subjects in the intervention group will receive a home-based disease management program based on the Theory of Dyadic Illness Management on the basis of the control group. The duration of the intervention is 3 months, and the follow-up is 6 months. Data is collected at enrolment, 3 months after the intervention, and 3 months after the end of the intervention. The primary outcome is patients' quality of life and readmission. Secondary outcomes include patients' self-management behaviors, anxiety, and depression and caregivers' quality of life and care burden. This study focuses on whether this home-based disease management program can improve the quality of life of elderly patients with CHF, reduce the readmission rate, enhance their self-management capacity, reduce negative emotions, and reduce the burden of informal caregivers. It can provide a new perspective on home management and cardiac rehabilitation of heart failure disease in the elderly, as well as alleviate problems such as the burden of healthcare resources. Chinese Clinical Trials Registry ChiCRT2300068026. Registered on 3 February 2023, manuscript Version: 1.0,  https://www.chictr.org.cn/ .